1988
DOI: 10.1063/1.339919
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of deep levels in zinc oxide

Abstract: An electron trap of 0.3 eV depth was characterized in hydrothermally grown, single-crystal zinc oxide using deep-level transient spectroscopy. Specimens were fabricated with Ag Schottky contacts on (0001) surfaces. The capture cross section was determined to be 2.6×10−14 cm2. The defect is a native donor and is attributed to a singly ionized oxygen vacancy V•O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
90
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(98 citation statements)
references
References 12 publications
8
90
0
Order By: Relevance
“…4 Various growth conditions also can influence the presence of midgap impurities and point defects and such deep centers can produce undesired trapping and carrier recombination. In past years, deep level transient spectroscopy ͑DLTS͒ has been used to study traps ͑mainly electron traps͒ in n-type bulk ZnO grown by the hydrothermal, 5 vapor-phase, 6 and pressurized melt growth 7 methods. In most of these cases, the DLTS test structures were Schottky-barrier diodes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Various growth conditions also can influence the presence of midgap impurities and point defects and such deep centers can produce undesired trapping and carrier recombination. In past years, deep level transient spectroscopy ͑DLTS͒ has been used to study traps ͑mainly electron traps͒ in n-type bulk ZnO grown by the hydrothermal, 5 vapor-phase, 6 and pressurized melt growth 7 methods. In most of these cases, the DLTS test structures were Schottky-barrier diodes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the number of shallow donors introduced by radiation will balance the number of radiation induced acceptors, we will not observe any drastic change in the free carrier concentration and neither will we detect any major DLTS peaks in the temperature domain investigated. This possibility will have to be verified by performing admittance spectroscopy measurements 12 to facilitate the detection of defect levels too deep to be detected by DLTS, and Hall and photoluminescence measurements to detect the shallow donors ͑too shallow to be detected by DLTS͒. At this point, it should be noted that Look et al have reported an increase in concentration of one of the shallow donors in ZnO after electron irradiation.…”
mentioning
confidence: 99%
“…Common to the majority of these reports for poly-or singlecrystalline ZnO, is the presence of a defect, L2, with a level situated around 0.3 eV below the conduction band. [8][9][10][11][12][13][14] In addition, single-crystal ZnO grown by the hydrothermal technique contains a defect with a level estimated at E C Ϫ0.34 eV, from temperature-dependent Hall-effect measurements; 1 this defect is probably related to L2. Another defect, L1, with a level reported between 0.18 and 0.23 eV, 8,10,12,13 has only been observed in poly-ZnO, but little is known about its identity.…”
mentioning
confidence: 99%